Electrocoagulation treatment of rice grain based distillery effluent using copper electrode. (June 2016) - Prajapati, Abhinesh Kumar; Chaudhari, Parmesh Kumar; Pal, Dharm; Chandrakar, Anil; Choudhary, Rumi
Abstract: This article reports the electro coagulation treatment (ECT) of rice grain based distillery effluent in a batch reactor using copper electrodes. ECT with copper electrode is a better alternative as compared to aluminum/iron electrode to treat rice grain based biodigester effluent (BDE), due to less power consumption at acidic pH which is the main attraction of the present work. The ECT in batch mode is conducted in a 1.5 L cubical shape electrocoagulation reactor using four-plate configurations. A current density of 89.3 A / m 2 and pH 3.5 is found to be optimal, providing a maximum chemical oxygen demand (COD) and colour removal of 80% and 65%, respectively. At pH 3.5 electrode loss was 3.667 mg/L and power consumption was 11.42 WH/L. It is noted that treated slurry at pH 8 has shown best settling characteristic, which decreases with decrease in pH. Thermogravimetric analysis indicates that the residues obtained from the EC treated BDE may be used as fuel.